A protocol for assessing the adhesion potential of lactic acid bacteria on various cell types - Lakshmi Jayaram; Ramith Ramu; Deepthi Puttegowda; Jayanthi M K; Chandana Kumari V B; Khang Wen Goh (STAR Protocols)
Summary: Lactic acid bacteria (LAB) are a large group produced during carbohydrate fermentation, resulting in lactic acid. Here, we present a protocol for probiotic adhesion and interaction into buccal epithelial cells, chicken epithelial cells, and HT-29 cells, as well as for autoaggregation and coaggregation. We describe steps for visualizing LAB adhesion by imaging cell adhesion using a light microscope. We then detail procedures for performing an adhesion assay.For complete details on the use and execution of this protocol, please refer to Kumari et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.